Modern and Systems-Oriented Research Methodology - M. Bunjamin Bunjamin (BATAN, 1998)
ABSTRACT This paper is to report the results of literature studies on the latest development of systems-oriented research methodology. Scientific communities effort to modernize research methodology is based on the fact that research is no longer of academic interest only, but it has become an integral part of modern business practices that highly infuenced by market dynamics. Consequently, there is a strong pressure on the research institutions that they should be able to achieve and produce concrete research results effectively, eficiently, and productively, as well as meeting rapidly change market demand. ABSTRAK Tulisan ini melaporkan hasil studi literatur tentang perkembangan metodologi penelitian modern berwawasan sistem. Maksud para peneliti untuk memutakhirkan metodologi penelitian ialah karena sekarang penelitian bukan memenuhi selera akademik saja, tetapi sudah menjadi bagian integral yang tak terpisahkan dari kegiatan bisnis modern, sehingga sangat dipengaruhi oleh dinamika pasar. Akibatnya, institusi penelitian sangat dituntut untuk mampu berprestasi dan mampu menghasilkan karya-karya penelitian nyata secara efektif, efisien, dan produktif, sekaligus mampu memenuhi permintaan pasar yang cepat berubah.